Peran Komite Untuk Peningkatan Mutu Lembaga Pendidikan di Madrasah Aliyah Negeri 4 Kabupaten Kediri - Nauval, M. Mirza Azizin (Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
Community involvement in education is embodied in the Madrasah Committee organization formed by each education unit. This organization aims to channel community aspirations and initiatives, responsibilities, community roles and a transparent, accountable and democratic atmosphere in the implementation of education can actually be realized. So that this goal is not just a slogan, a strategy is needed so that the role of the Madrasah Committee can be optimal and can contribute to education so that the quality of education is increasing. Based on the description above, it can be formulated a problem formulation, first, how the tasks carried out by the Madrasah Committee in improving the quality of education in Madrasah Aliyah Negeri 4 Kediri Regency. Second, how is the function carried out by the Madrasah Committee in improving the quality of education in Madrasah Aliyah Negeri 4 Kediri Regency. This research use desciptive qualitative approach. There are 3 kinds of data collection methods used by researchers, namely the observation method, the interview method, and the documentation method. Analysis of the data in this study by recording data from interviews, observations and documentation, organizing the data, sorting it out to answer the formulation of the problem then looking for and finding meanings related to the formulation of the problem. The results of the study, first, the Madrasah Committee's duties are as an advisory agency in all activities carried out, a supporter (supporting agency), controller (controlling agency) and a mediator or liaison between parents and schools to make a superior school or madrasah. The Madrasah Committee is running well. Second, the function of the Madrasah Committee is to encourage public attention and commitment to the implementation of quality education, to collaborate with the community (individuals/organizations/business/industrial world) and the government regarding the provision of quality education, to accommodate and analyze aspirations, ideas, demands. and various educational needs proposed by the community, providing input, considerations, and recommendations to the education unit regarding: education policies and programs, RAPBS, educational unit performance criteria, education personnel, educational facilities, and so on, encouraging parents and the community to participate in education in order to support the improvement of the quality and equity of education, to raise public funds in financing the implementation of education in the education unit, to evaluate and supervise the policies, programs, implementation, and outputs of education in the education unit. From these results, the researcher suggests that these tasks and functions be maintained and further developed so that the role of the Madrasah Committee is more optimal so that the quality of education in Madrasah Aliyah Negeri 4 Kediri Regency is increasing.